(untitled) (Journal of Medical & Health Sciences Review, 2025)
OBJECTIVE: To compare krimsky test and prism cover test for evaluation which test is better for measurement of angle of deviation among squint patients. MATERIALS AND METHODS: A cross-sectional study was conducted at eye out patient department (OPD) of Shalamar Hospital, Lahore from August 2023 to January 2024. Data of 34 children (either gender, 6-16 years, concomitant strabismus) was collected using non-probability purposive sampling technique. Patients with incomitant strabismus, any other ocular pathology and those with any ocular surgery were excluded. All tests were performed using standard protocols. Data analysis was done using SPSS 25. Numerical data like age and qualitative data like gender, history like family, fever, trauma, patching, spectacles, surgery, when crossing of eyes first observed by parents, etc. were presented in the form of Frequency (Percentage). After fulfilling the desired parameters, Chi-square test was used to determine the association between Krimsky test & Prism cover test. RESULTS:A total of 34 children (16 males and 18 females) were recruited for this study from the age of 6 to 16 years, with an average mean age ± standard deviation of 2.921±3.294 years. 11 participants out of 34 had myopia(32.4%), 13 had hypermetropia (38.2%), 4 had astigmatism(11.8%), 6 were emmetrope (17.6%). When the Kimsky and PCT were done for comparison patients with <30 PD were 13(38.2%), 30- 45PD were 12(35.3%), 45-60PD were 5(14.7%) and 60-75PD were 4(11.8%). The p- value was less than 0.05(p-value 0.001) which means results were significant. CONCLUSION:Frequency of females were higher than males but had no significant association of age, gender, family history, history of trauma, history of fever with the strabismus. Although strong correlation was found between krimsky and prism cover test as p value was less than 0.05 (<0.001).